THE CONTRIBUTION OF ENDOCRINE DISRUPTING HEAVY METALS TO OESTRADIOL MODULATION AND SEMEN QUALITY NIGERIAN MEN (2011)
Declining male fertility is of global concern and has been linked to the effects of endocrine disruptors on the modulation of oestradiol. These disruptors are also recognised to be toxic to the testes. Selenium and zinc play specific roles in heavy metal detoxification, testosterone metabolism, sperm formation and motility. This study was aimed at identifying the possible contribution of cadmium, lead, selenium and zinc to oestradiol modulation and sperm defects in Nigerian men. One hundred and twenty males (20-54 years) were recruited after informed consent. These were age-matched 77 dyspermics and 43 normospermics recruited from the Urology Clinics of two teaching hospitals in Nigeria. Demographic and anthropometric indices were obtained using a structured questionnaire and standard methods respectively. Semen samples were collected from subjects by masturbation after 3-5 days of abstinence from sexual intercourse. Spermiogram and sperm morphological characteristics were done using WHO guidelines and Tygerberg strict criteria respectively. Ten milliliters of blood was obtained from each participant. Serum and seminal plasma were obtained by centrifugation of clotted blood and semen respectively. Testosterone, oestradiol, prolactin, luteinizing hormone and follicle stimulating hormone were estimated in serum while testosterone and oestradiol were estimated in seminal plasma by enzyme immunoassay method. Cadmium, lead, selenium and zinc were assayed in serum and seminal plasma by atomic absorption spectrophotometry. Data were analysed using t-test, ANOVA and multiple regressions at p=0.05. Forty-eight (62.3%) dyspermics had reduced sperm motility and abnormal morphology while 17 (22%) and 12 (15.6%) had oligospermia and azoospermia respectively. Seminal plasma UNIVERSITY OF IBADAN LIBRARY iii oestradiol was significantly lower in normospermics (0.7±0.04nmol/L) than dyspermics (1.1±0.07nmol/L) while testosterone/oestradiol ratio was significantly higher in normospermics (10.7±0.60) than dyspermics (7.3±0.70). Serum and seminal plasma cadmium were significantly higher in dyspermics (0.3±0.02μg/L; 2.0±0.07μg/L) than normospermics (0.1±0.01μg/L; 1.2±0.07μg/L) respectively. Serum and seminal plasma lead levels were also significantly higher in dyspermics (34.8±0.55μg/dL; 39.2±0.61μg/dL) than normospermics (28.2±0.74μg/dL; 31.9±0.87μg/dL), respectively. Serum and seminal plasma selenium were significantly higher in normospermics (0.9±0.01mg/L; 0.3±0.01mg/L) than dyspermics (0.8±0.01mg/L; 0.2±0.01mg/L) respectively. Serum and seminal plasma zinc were significantly higher in normospermics (7.9±0.16mg/L; 161.9±5.16mg/L) than dyspermics (7.2±0.12mg/L; 141.9±2.77mg/L) respectively. In dyspermic men, increased serum Cd was significantly associated with increased oestradiol in serum (β=0.42) and seminal plasma (β=0.52). Increased seminal plasma Cd was associated with decreased seminal plasma Zn (β =-0.21), decreased % motility (β =-1.03), increased % tail defects (β =0.08) and decreased sperm deformity index (β =-0.21). Increased serum Pb was significantly associated with serum FSH (β = 0.29). Increased seminal plasma Pb was significantly associated with increased serum FSH (β = 0.21). Increased sperm count was significantly associated with decreased serum oestradiol (β =-0.75) and testosterone/oestradiol ratio (β = -0.54); increased seminal plasma oestradiol (β =0.41) and testosterone/oestradiol ratio (β =0.38). Higher sperm deformity index was significantly associated with decreased serum Se/Pb ratio (β =-0.27). UNIVERSITY OF IBADAN LIBRARY iv Cadmium and Pb may cause depletion of Zn and Se which may account for the loss of their protective effect resulting in dyspermia through direct toxicity, oxidative stress, endocrine disruption or other yet unresolved mechanisms. Keywords: Oestradiol, Endocrine disruptors, Trace elements, Semen quality, Male fertility Word count: 494